Integrating psychological and mental health perspectives in disease management: improving patient well-being - Francesca Grosso (Humanities & Social Sciences Communications)
An interdisciplinary approach to healthcare highlights the significant role of collaboration between healthcare professionals to ensure comprehensive patient care. Integrative approaches in disease management are essential to improving patient outcomes and healthcare quality, as they emphasize interdisciplinary collaboration, effective doctor-patient communication, and the incorporation of cultural perspectives into medical practice. The pitfalls of fragmented care and absent teamwork between healthcare professionals often result in a narrow medical perspective, which negatively impacts patient outcomes. In this process, doctor-patient communication is a key factor in providing quality care and improving health outcomes. Communication gaps between health professionals and patients, influenced by beliefs and expectations, risk giving rise to two errors that can compromise the therapeutic alliance: the concept of self-fulfilling prophecy and the nocebo effect. To address these challenges, it is crucial to prioritize effective communication strategies that enhance patient understanding and foster shared decision-making. Furthermore, integrating a Bayesian interpretation of the human mind into healthcare helps discourage reliance on a singular perspective, ensuring a broader understanding of patient needs and contexts informs medical decisions. Looking forward, the adoption of a comprehensive, multidisciplinary approach to patient treatment and the incorporation of patient preferences into treatment decisions can enable continuous learning among healthcare professionals, ultimately contributing to a truly patient-centered healthcare system.